Memoria Anual 2024 : Instituto de Ingeniería Rural (IIR) - Instituto Nacional de Tecnología Agropecuaria (INTA). Instituto de Ingeniería Rural (Instituto de Ingeniería Rural, INTA, 2025)
This annual report describes the activities carried out during the year 2024.